Analisis Kapasitas Tampungan Embung Bulakan Untuk Memenuhi Kekurangan Kebutuhan Air Irigasi Di Kecamatan Payakumbuh Selatan - Garsia, Dafit; Sujatmoko, Bambang; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The dry season often causing hundreds of hectares of rice fields suffer from drought, coupled with reduced discharge of irrigation water sources. This problem can be experienced by  the farmers in various areas, including in the District of  South Payakumbuh. As an alternative to solving the problem if there is such a thing is to build a small dam that is used to store water for the rainy season and used for the dry season. This paper will discuss about availability of water, irrigation water requirements, analyze capacity small dam, operating time opening the sluicegate,  rice area  which can be irrigated  and calculate the  dimensions  of the  spillway. From the calculation of available water discharge approximately 159.33 l / dt, maximum irrigation water requirement of 1.204 l/sec/ha,  the maximum reservoir for irrigation around 12577.177 m3. Rice area which can be  irrigated calculated every hour on each opening  the sluicegate as high as 0.1 m, 0.15 m, 0.20 m, 0.25 m, and 0.30 m for 10 hours and a maximum rice area which can be irrigated successively measuring 195.424 ha, 284.876 ha, 368.494 ha, 445.991 ha and 517.042 ha in the first hour. Furthermore, at the tenth hour rice area which can be irrigated successively an area of 182.966 ha, 237.896 ha, 268.727 ha, 276.084 ha and 261.411 ha. Spillway using Ogee type summit with a summit height of 7.94 m and 1 m high surveillance. Keywords: small dam, water requirements, storage capacity